2014
DOI: 10.3174/ajnr.a4081
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Carotid Aneurysms in the Era of Flow Diversion: A Need to Revisit Treatment Paradigms

Abstract: BACKGROUND AND PURPOSE:Recent techniques of endoluminal reconstruction with flow-diverting stents have not been incorporated into treatment algorithms for cavernous carotid aneurysms. This study examines the authors' institutional experience and a systematic review of the literature for outcomes and complications using the Pipeline Embolization Device in unruptured cavernous carotid aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
0
29
1
3
Order By: Relevance
“…15 Several investigators advocate ICA sparing therapy with flow diverters for ICA aneurysms, also in patients who can tolerate ICA occlusion. 22 However, recent meta-analyses that concern flow-diverter stents show that the combined morbidity and mortality rate is approximately 10%, regardless of the type of aneurysm. [23][24][25][26][27][28][29] Mortality was 4% in the study of Briganti et al 24 in 76 patients with cavernous aneurysms treated with flow diverters.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several investigators advocate ICA sparing therapy with flow diverters for ICA aneurysms, also in patients who can tolerate ICA occlusion. 22 However, recent meta-analyses that concern flow-diverter stents show that the combined morbidity and mortality rate is approximately 10%, regardless of the type of aneurysm. [23][24][25][26][27][28][29] Mortality was 4% in the study of Briganti et al 24 in 76 patients with cavernous aneurysms treated with flow diverters.…”
Section: Discussionmentioning
confidence: 99%
“…The process of aneurysm occlusion after FDD placement is also linked in part to the antiplatelet regimen administered. 73 Potential occlusion of the side branches or perforating arteries carries the risk of secondary ischemic complications. Further, overlap of FDDs potentially increases the risk of arterial branch or perforator occlusion and may be responsible for ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In select cases, access to the cavernous sinus via surgical access to the superior ophthalmic vein or direct transorbital puncture through the superior orbital fissure can also be attempted 19. Tanweer et al 13 treated one CCF with transvenous access via the ipsilateral facial vein, superior ophthalmic vein to the cavernous sinus. Generally, transvenous embolization more effectively treats indirect CCFs rather than direct CCFs.…”
Section: Discussionmentioning
confidence: 99%
“…13 Tanweer et al 13 reviewed their experience of CCA treatment with the PED and reported one CCF among a group of 41 patients with 43 treated CCAs at 6-month follow-up. The fistula was incidentally discovered and treated transvenously, as described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation